Characteristics of Culturable Microbial Community in Rhizosphere/Non-rhizosphere Soil of Potentilla Fruticosa Population in Alpine Meadow Elevation Gradient - Liu, Minxia; Li, Bowen; Xu, Lu; Yu, Ruixin (Frontiers in Soil Science, 2021)
Potentilla fruticosa is a typical shrub of alpine meadow, canopy effects can greatly influence soil fertility and microbiological parameters, and the changes of rhizosphere microorganisms also can reflect the response of the plants to environmental changes. The aim of study was to examine the rhizosphere and non-rhizosphere of Potentilla fruticosa on the amount of selected microorganisms and main environmental factor at different elevation gradient (3000 m, 3250 m, 3500 m, 3750 m and 4000 m). The results suggested that bacteria were predominant of the microbial soil community in rhizosphere and non-rhizosphere, while fungi and actinomycetes represented the minority. With the increase of altitude, the total amount of microbial, bacteria and actinomycetes in rhizosphere and non-rhizosphere of Potentilla fruticosa showed an downward trend, and microbial functional groups showed “hump shape” changed, but the fungi is the opposite. Variance inflation factor (VIF) screening environmental factors and path analysis can be obtained: in the rhizosphere soil, bacteria were affected by SOC, and SBD became the main environmental limiting factor with the increase of altitude. The main environmental limiting factor of actinomycetes changed from SBD to ST. In the non-rhizosphere soil, the bacteria and actinomycetes changed from ST to SOC and SBD, respectively. And the main environmental limiting factor of the fungi was SOC in rhizosphere and non-rhizosphere. SWC was main environmental determinant factors for all microbial groups, microbial functional groups were related to STN. Our results can help to understand the relationship between nutrient cycling and ecosystem function of alpine meadow plants soil microorganisms, and provide theoretical support for alpine meadow ecosystem restoration, biodiversity protection and microbial resources utilization.